Clinical profile of thyrotoxicosis and related cardiovascular morbidities among patients attending endocrine outpatient department in a tertiary care centre - Khandait, Harshwardhan V.; Ambulkar, Sunil G.; Tayde, Parimal S. (International Journal of Research in Medical Sciences, 2019)
Background: Thyroid disorders are common in India. Symptoms and signs of thyrotoxicosis are nonspecific. Graves disease is an autoimmune condition and is the most common cause of thyrotoxicosis. Cardiovascular system is frequently affected in thyroid disorders but there is not much data on prevalence of thyrotoxicosis and related cardiovascular morbidities in central India. Objectives of study the clinical profile of patients with thyrotoxicosis and outline the related cardiovascular manifestations in a tertiary care center. Design-over a period of nine months a descriptive cross sectional study was conducted in a tertiary health care center. Methods: A total of 150 patients with thyrotoxicosis were studied. Patients with known diagnosis of thyrotoxicosis and newly diagnosed cases were included. The participants were investigated for thyroid profile, Electrocardiogram, Complete blood count, serum electrolytes and kidney function test. Results: Out of 150 patients of thyrotoxicosis, 87 (58 %) were diagnosed with Graves’s disease. Hypertension was observed in 78 (52 %) of participants. Atrial fibrillation was found in 18 (12%) and sinus tachycardia in 53 (35.33 %) of the participants. Conclusion: Grave’s disease is the commonest cause of thyrotoxicosis. Hypertension, sinus tachycardia and Atrial Fibrillation are the common cardiovascular diseases observed to be associated with thyrotoxicosis.